2004
DOI: 10.1097/01.ju.0000135402.56109.cf
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Injury in Children: Long-Term Urodynamic and Urological Outcomes

Abstract: To our knowledge this is the largest and longest urological study of young children with SCI. Early clean intermittent catheterization and use of anticholinergics appear to prevent upper tract deterioration, improve continence and decrease infections. Serial urodynamics confirm increasing safe capacity with growth in most children. Close followup is necessary as bladder characteristics may change with time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
9

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 11 publications
0
25
0
9
Order By: Relevance
“…20 The ICI-CDT recommends that UDS in children with SCI is planned on an individual basis, but not earlier than 6 weeks after injury.…”
Section: Urodynamic Testing In Patients With Relevant Neurologic Abnomentioning
confidence: 99%
“…20 The ICI-CDT recommends that UDS in children with SCI is planned on an individual basis, but not earlier than 6 weeks after injury.…”
Section: Urodynamic Testing In Patients With Relevant Neurologic Abnomentioning
confidence: 99%
“…Other studies also reported that close follow-ups were necessary and appropriate urinary management, which is dependent on the neurological level and type of injury, needed to be conducted for pediatric SCI patients because urodynamic characteristics, including other neurological characteristics, may change with natural growth. 3,4 Thus, urinary management needs to be reconsidered based on the findings of urodynamic evaluations during long-term follow-ups in pediatric SCI patients.…”
Section: Discussionmentioning
confidence: 99%
“…10 Furthermore, since abnormalities such as scoliosis, kyphosis, lordosis and syringomyelia may occur in SCI children with long-term follow-ups, which may induce neurological deterioration, 11 LUT function may be altered during follow-ups with an impact on the kidneys and upper urinary tract. 4,12 Therefore, urodynamics need to be performed in all SCI patients who start or continue self-voiding during follow-ups. Continence is a major issue for many patients on reflex voiding due to spontaneous contractions of the detrusor muscle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors conclude that with early introduction of CSIC and anticholinergic medications the upper tract changes could be minimised. 10 The aim of this retrospective review is to observe evolution of management over time, report adult urological outcomes and complications in paediatric onset SCI.…”
Section: Introductionmentioning
confidence: 99%